Etofenamate Levels in Human Serum and Synovial Fluid Following Iontophoresis - Bender, Tamás; Bariska, János; Rojkovich, Bernadette; Bálint, Géza (Arzneimittelforschung, 2001)
The absorption of etofenamate (CAS 30544-47-9, Rheumon® gel) by iontophoresis in 11 patients with low back pain and in 13 patients with synovitis of the knee was evaluated. During the 5-day treatment period, the test gel in a quantity corresponding to 100 mg etofenamate was applied to affected body regions every day by 20-min iontophoresis sessions.Two hours after the fifth application, the concentration of etofenamate in serum and synovial fluid (in patients who had knee joint iontophoresis) were measured by HPLC. Iontophoresis of etofenamate into the lumbar region as well as to the knee joint resulted in consistent serum levels: 219 ± 136.3 μg/l and 191 ± 84.6 μg/l, respectively. In patients with synovitis of the knee, the synovial level of etofenamate (368 ± 109.2 μg/l) was almost twice as high than the serum concentration. The authors conclude that with topical application of etofenamate by iontophoresis the drug appears not only in the serum but also - with higher levels - in the synovial fluid.
Keywords: CAS 30544-47-9; Etofenamate, serum levels, synovial fluid levels; Iontophoresis; Rheumon® gel